EFFECT ON INQUIRY LEARNING MODEL STUDENT LEARNING OUTCOMES OF THE SUBJECT MATTER OF TEMPERATURE AND IN CLASS X CALORIFIC SEMESTER II SMA SWASTA IMELDA MEDAN A.Y 2016/2017 - Rina, Rina; Purwanto, Purwanto (JURNAL IKATAN ALUMNI FISIKA UNIVERSITAS NEGERI MEDAN, 2018)
This study aims to determine the effect of inquiry learning model to the learning outcomes of students in the subject matter of temperature and heat in SMA Swasta Imelda Medan A.Y. 2016 / 2017. Type this research is quasi experiment. The population in this study were all students of class X Semester II, which consists of three classes. Sampling was done by cluster random sampling. By taking two classes of third grade at random, that is class X-l as the experimental class using inquiry learning model and a class X-2 as the control class using conventional learning, each of which amounted to 32 people. The instrument used was a test of student learning outcomes that are 20 questions in the form of multiple choice and activity observation sheet. Hypothesis testing using t test with level Î± = 0,05. Result initial testing with pre-test values obtained average pretest experimental class is 48.28, and the average value pretest control class is 44.53. Pretest data testing through the second sample normality test showed normal distribution. In the homogenous eity test obtained Fcount = 108 and = 2.37 Ftable so Fhitung < Ftable then both samples come from a homogenous ous group. The results of data analysis of test two parties obtained tcount = 1.962 < ttable = 1,999 so that Ho accepted to mean both classes of the samples had the same initial capability. The average value postes experimental class and control class = 71.41 = 62.50. The results oft test analysis of the obtained t = 3.835 and ttable = 1.667 so thitung > ttable then Ho rejected and Ha accepted means there is significant influence inquiry learning model to the learning outcomes of students in the subject matter of temperature and heat in the tenth grade second semester SMA Swasta Imelda Medan A.Y 2016/2017.